Initial Testing of NSC 750854, a Novel Purine Analog, Against Pediatric Tumor Models by the Pediatric Preclinical Testing Program. Issue 3 (24th November 2015) - Gorlick, Richard; Kolb, E. Anders; Keir, Stephen T.; Maris, John M.; Lock, Richard B.; Carol, Hernan; Reynolds, C. Patrick; Kang, Min H.; Billups, Catherine A.; Collins, Jerry; Kurmashev, Dias; Kurmasheva, Raushan T.; et al.
Abstract : Background: NSC 750854 is a purine analog with an antitumor activity profile distinctive from that of other anticancer purines. It has shown significant activity against adult cancer preclinical models. Procedure: NSC 750854 was tested against the Pediatric Preclinical Testing Program (PPTP) in vitro cell line panel at concentrations from 1.0 nM to 10 μM and against the PPTP in vivo xenograft panels administered intraperitoneally at a dose of 5 mg/kg daily for 5 days repeated at day 15. Results: The median relative IC50 (rIC50 ) value for the PPTP cell lines was 32 nM (range from 11 to 124 nM), with consistent cytotoxicity across all cell lines. Acute lymphoblastic leukemia (ALL) cell lines were more sensitive to NSC 750854 than non‐ALL cell lines. NSC 750854 induced significant differences in EFS distribution compared to control in 31 of 35 (89%) solid tumor xenografts. It induced tumor growth inhibition meeting criteria for intermediate or high event free survival (EFS) T/C activity in 17 of 32 (53%) evaluable solid tumor xenografts (most consistently in the rhabdomyosarcoma panel). Objective responses were observed in 15 of 37 (41%) solid tumor xenografts and in all eight leukemia models with complete response (CR) or maintained complete response (MCR) in seven of eight leukemia models. Conclusions: NSC 750854 has a unique spectrum of antitumor activity compared with other agents tested by the PPTP as it induces regression in tumor models with limited sensitivity to most agents tested to date. Given the promising level of activity observed for NSC 750854 against PPTP preclinical models, further exploration of its mechanism of action is warranted.